A Complete Treatment of Adult Living Donor Liver Transplantation: A Review of Surgical Technique and Current Challenges to Expand Indication of Patients. Issue 1 (30th October 2014) - Lee, S.‐G.
<x xml:space="preserve">Abstract</x> The growing disparity between the number of liver transplant candidates and the supply of deceased donor organs has motivated the development of living donor liver transplantation (LDLT). Over the last two decades, the operation has been markedly improved by innovations rendering modern results comparable with those of deceased donor liver transplantation (DDLT). However, there remains room for further innovation, particularly in adult living donor liver transplantation (ALDLT). Unlike whole‐size DDLT and pediatric LDLT, size‐mismatching between ALDLT graft and recipient body weight and changing dynamics of posttransplant allograft regeneration have remained major challenges. A better understanding of the complex surgical anatomy and physiologic differences of ALDLT helps avoid small‐for‐size graft syndrome, graft congestion from outflow obstruction and graft hypoperfusion from portal flow steal. ALDLT for high‐urgency patients (Model for End‐Stage Liver Disease score >30) can achieve results comparable to DDLT in high volume centers. Size limitations of partial grafts and donor safety issues can be overcome with dual grafts and modified right‐lobe grafts that preserve the donor's middle hepatic vein trunk. Extended application of LDLT for unresectable hepatocellular carcinoma above Milan criteria is an optional strategy at the cost of slightly compromised survival. ABO‐blood group incompatibility obstacles have been broken down by introducing a paired donor exchange program and refined peri‐operative management of ABO‐incompatible ALDLT. This review focuses on recent innovations of surgical techniques, safe donor selection, current strategies to expand ALDLT with broadened patient selection criteria and important aspects of teamwork required for success.